Hypoglycemic and Hypocholesterolemic Effects of Lesser yam Synbiotic Yoghurt (Dioscorea Esculenta L) on Metabolic Syndrome Wistar Rats - Rosida; Santi, Sintha Soraya (Journal Akademik Universitas Swiss German, 2023)
This study aims to determine the effect of consumption of lesser yam synbiotic yoghurt on glucose levels and blood lipid profiles of metabolic syndrome rats. Synbiotic yoghurt has positive effect on health such as increasing body immunity, lowering blood glucose and cholesterol levels. In this study, lesser yam synbiotic yoghurt was made from cow's milk and lesser yam extract with (1:1) proportion, sugar, skim milk and starter of lactic acid bacteria and then followed by bioassay test using experimental rats. The results showed that lesser yam synbiotic yoghurt can reduce glucose levels and improve the blood lipid profile of rats. The best treatment is to give 4 ml of synbiotic yoghurt per day which can reduce glucose levels and total blood cholesterol of metabolic syndrome rats. It can be concluded that lesser yam synbiotic yoghurt which had high levels of dietary fiber and inulin, had hypoglycemic and hypocholesterolemic effect.